Feasibility study of Aesculus turbinata fruit shell-derived biochar for ammonia removal in wastewater and its subsequent use as nitrogen fertilizer - Lee, Jae In; Jadamba, Chuluuntsetseg; Lee, Chang Gu; Hong, Sung Chang; Kim, Jin Ho; Yoo, Soo Cheul; Park, Seong Jik (Chemosphere, 2024)
In the face of increasing nitrogen demand for crop cultivation driven by population growth, this study presents a sustainable solution to address both the heightened demand and the energy-intensive process of nitrogen removal from wastewater. Our approach involves the removal of nitrogen from wastewater and its subsequent return to the soil as a fertilizer. Using biochar derived from Aesculus turbinata fruit shells (ATFS), a by-product of post-medical use, we investigated the effect of pyrolysis temperature on the NH4–N adsorption capacity of ATFS biochar (ATFS-BC). Notably, the ATFS-BC pyrolyzed at 300 °C (ATFS-BC300) exhibited the highest NH4–N adsorption capacity of 15.61 mg/g. The superior performance of ATFS-BC300 was attributed to its higher number of oxygen functional groups and more negatively charged surface, which contributed to the enhanced NH4–N adsorption. The removal of NH4–N by ATFS-BC300 involved both physical diffusion and chemisorption, with NH4–N forming a robust multilayer adsorption on the biochar. Alkaline conditions favored NH4–N adsorption by ATFS-BC300; however, the presence of trivalent and divalent ions hindered this process. Rice plants were cultivated to assess the potential of NH4–N adsorbed ATFS-BC300 (NH4-ATFS-BC300) as a nitrogen fertilizer. Remarkably, medium doses of NH4-ATFS-BC300 (594.5 kg/ha) exhibited key agronomic traits similar to those of the commercial nitrogen fertilizer in rice seedlings. Furthermore, high doses of NH4-ATFS-BC300 demonstrated superior agronomic traits compared to the commercial fertilizer. This study establishes the viability of utilizing ATFS-BC300 as a dual-purpose solution for wastewater treatment and nitrogen fertilizer supply, presenting a promising avenue for addressing environmental challenges.
Keywords: Adsorption capacities; Agronomic traits; Ammonia removal; Ammonia-nitrogen; Biochar; Crop cultivation; Feasibility studies; Plant growth; Population growth; Sustainable solution; Adsorption; Ammonia; Charcoal; Feasibility Studies; Fertilizers; Fruit; Nitrogen; Oryza; Waste Disposal, Fluid; Wastewater; Water Pollutants, Chemical; Adsorption; Ammonia nitrogen; Biochar; Fertilizer; Plant growth